Agensi Pasif: Refleksivitas dan Rasionalitas Perempuan Perokok di Yogyakarta - Haq, Ahmad Nadhif; Sujibto, B.J. (Prodi Sosiologi Agama, 2023)
This article analyzes how young women smokers defend themselves and perpetuate their smoking activity in an environment that rejects it through discursive understanding as the basis for their actions. In addition, this study discusses how women smoke and take into account smoking activity, social aspects, and physical aspects around it. The theoretical approach used is the agency theory of ​​Anthony Giddens which deeply considers the aspects of managed reflexivity. This theory underlines that a continuous flow or stream of acts is inherently constructed by a process of rationalizing actions to underlie the agent's actions through reflexive monitoring. This study uses qualitative methods to obtain in-depth information from primary sources, namely smoking women in Yogyakarta. To support primary data, observation and documentation are used as secondary data sources. This article scrutinizes (1) women as social agents reflect the surrounding norms, smoking ethics, their body's acceptance of smoking, and their health risks, (2) women smokers rationalization their actions with a practical and discursive basis include the history of smoking women, gender equality, discourse on pharmaceutical interests, and culturally expressed self-freedom, and (3) smoking women are passive agents, namely agents who act within the limits of the structure but have power over themselves. to express themselves.